Antibacterial Efficay Test of Ethanol Extract of Yaki Areca Nut (Areca vestiaria) Against the Growth of Propionibacterium acnes, the Cause of Acne. - Pabundu, Daniel; Simbala, Herny; Hariyanto, Yuanita Amalia (UNIVERSITAS SAM RATULANGI, 2024)
A bacterial skin infection that is often experienced by everyone, especially in adolescence, is acne(Acne vulgaris). Acne is caused by the accumulation of excess oil in the skin, thus becoming a medium for bacterial growth, which causes acne. The use of natural antibiotics can be a therapeutic option in the treatment of acne. One of the plants that potentially has antbacterial activity is Pinang Yaki (Areca vestiaria). The purpose of this study was to determine the antibacterial activity of ethanol extract of areca nut fruit against the growth of Propionibacterium acnes that causes acne. The test of antibacterial activity of areca nut extract with the pitting method found that at a concentration of 10% the antibacterial activity was included in the weak group, 20% was included in the medium group, while those included in the strong group in inhibiting the growth of Propionibacterium acnes were extracts with concentrations of 40%, 60% and 80%..